Seed germination of Phacelia secunda (Boraginaceae) and Eryngium paniculatum (Apiaceae), perennial herbs from Patagonia Argentine - Chichizola, Giselle Ailin (2019)
The aim was to evaluate the seed germination requirements of Phacelia secunda J.F. Gmel. and Eryngium paniculatum Cav. y Dombey ex F. Delaroche, perennial herbaceous colonizers of degraded environments of northwest Argentinian Patagonia and of interest for ecological restoration. The germination percentage, mean germination time and time until initiation of germination of a control (C) and two pre-germination treatments: mechanical scarification with a scalpel (EM) and 45 days cold moist stratification (EHF) were evaluated. In P. secunda, the germination percentage in EHF treatment (2%) was lower than in C (24%) and EM (16%) treatment. In E. paniculatum, differences between C (94%) and EHF (82%) were found, but not between C and EM (91%). EHF treatment accelerated the germination initiation in both species. Seeds of P. secunda showed low germination capacity being necessary to evaluate new treatments. Eryngium paniculatum showed high germination capacity in the control. Thus this species does not require specific pre-germination treatments.